2017
DOI: 10.1021/acs.jnatprod.6b00977
|View full text |Cite
|
Sign up to set email alerts
|

α-Glucosidase Inhibitors from Malbranchea flavorosea

Abstract: From an extract prepared from the grain-based culture of Malbranchea flavorosea two new polyketides, namely, 8-chloroxylarinol A (1) and flavoroseoside (2), along with the known compounds xylarinol A (3), xylarinol B (4), massarigenins B and C (5 and 6), and clavatol (7), were isolated. The structures of 1 and 2 were elucidated using spectroscopic methods and corroborated by single-crystal X-ray diffraction analysis. In the case of compound 2 the absolute configuration at the stereogenic centers was establishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…Docking of 32 to hNt-MGAM and hCt-MGAM as well as to hNt-SI and y-IM predicted that it would bind to them far from the catalytic site; the interacting forces were mainly by hydrophobic contacts and hydrogen bonding (HB). The overall docking results were consistent with the in vitro α-glucosidase inhibitory properties of compound 32 and predicted that its inhibitory action could be exerted throughout an allosteric interaction with the enzymes [25]. Further research is in progress to assess how it is absorbed, distributed, metabolized, and excreted.…”
Section: Fungal Endophytes From Hintonia Latiflorasupporting
confidence: 68%
See 2 more Smart Citations
“…Docking of 32 to hNt-MGAM and hCt-MGAM as well as to hNt-SI and y-IM predicted that it would bind to them far from the catalytic site; the interacting forces were mainly by hydrophobic contacts and hydrogen bonding (HB). The overall docking results were consistent with the in vitro α-glucosidase inhibitory properties of compound 32 and predicted that its inhibitory action could be exerted throughout an allosteric interaction with the enzymes [25]. Further research is in progress to assess how it is absorbed, distributed, metabolized, and excreted.…”
Section: Fungal Endophytes From Hintonia Latiflorasupporting
confidence: 68%
“…The last fungus selected for the search of α-glucosidase inhibitors was M. flavorosea. From the active extract prepared from the grain-based culture, two new polyketides, namely, 8-chloroxylarinol A (27) and flavoroseoside (28), along with the known compounds xylarinol A (29), xylarinol B (30), massarigenins B and C (31 and 32), and clavatol (33), were isolated [25] (▶ Fig. 5).…”
Section: Fungal Endophytes From Hintonia Latifloramentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this side effects and other constraints; patients now prefer to use locally available herbs to treat diabetes, especially those plant and plant parts that are already consumed as food or food condiments since these plants have been seen to have lower side effects and are quite affordable. Several plants have been reported to have alphaglucosidase inhibitory activity (32)(33)(34)(35). Momordica charantia being one of such plants, also the fact that several types of research (13)(14)(15)(16)(17) have shown the potency of the plant in the management of diabetes, it, therefore, justifies the focus of this particular research.…”
Section: Discussionmentioning
confidence: 93%
“…As shown for a few examples in Tables 2-4 which consist in a sampling of recently reported works on natural compounds, this "Systematism" is already used by a few groups who catalogued the chemical compounds in a given organ of a given plant (Batista et al, 2017;Sendker et al, 2017;Ma et al, 2018;Sharma et al, 2018), in a fungus (Chang et al, 2017), or in a microorganism (McMullin et al, 2017;Verastegui-Omana et al, 2017). In such cases, an idea of the possible diversity of those sources is given.…”
Section: At the Development Stage: Systematic Inventories Of Natural mentioning
confidence: 99%